Your Spouse Is Fired! How Much Do You Care? - Milena Nikolova; Sinem H. Ayhan (Institute of Labor Economics (IZA), 2016)
This study is the first to provide a causal estimate of the subjective well-being effects of spousal unemployment at the couple level. Using German panel data on married and cohabiting partners for 1991-2013 and information on exogenous job termination induced by workplace closure, we show that spousal unemployment reduces the life satisfaction of indirectly-affected spouses. The impact is equally pronounced among female and male partners. Importantly, the results are not driven by an income effect, but likely reflect the psychological costs of unemployment. Our findings are robust to a battery of sensitivity checks and imply that public policy programs aimed at mitigating the negative consequences of unemployment need to consider within-couple spillovers.
Keywords: I31; J01; J65; 330; unemployment; involuntary job loss; plant closure; spouses; well-being